2018
DOI: 10.1002/aic.16418
|View full text |Cite
|
Sign up to set email alerts
|

Rapid CO2 capture from ambient air by sorbent‐containing porous electrospun fibers made with the solvothermal polymer additive removal technique

Abstract: Direct air capture (DAC) of CO 2 is an emerging technology in the battle against climate change. Many sorbent materials and different technologies such as moisture swing sorption have been explored for this application. However, developing efficient scaffolds to adopt promising sorbents with fast kinetics is challenging, and very limited effort has been reported to address this critical issue. In this work, the availability and kinetic uptake of CO 2 in sorbents embedded in various matrices are studied. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
0
19
0
2
Order By: Relevance
“…The authors report the new sorbent has a faster CO 2 sorption rate than other reported sorbents . Since then, Armstrong et al., Song et al., and Hou et al . each reported their own newly developed sorbent to have a shorter half‐time—i.e.…”
Section: Sorbents For Co2 Capture From Airmentioning
confidence: 97%
See 1 more Smart Citation
“…The authors report the new sorbent has a faster CO 2 sorption rate than other reported sorbents . Since then, Armstrong et al., Song et al., and Hou et al . each reported their own newly developed sorbent to have a shorter half‐time—i.e.…”
Section: Sorbents For Co2 Capture From Airmentioning
confidence: 97%
“…[262] Shi et al [88] developed anew moisture-swing CO 2 sorbent with an ion-exchange resin (IER) and ap olyvinyl chloride (PVC) as binder.T he authors report the new sorbent has af aster CO 2 sorption rate than other reported sorbents. [88] Since then, Armstrong et al, [263] Song et al, [264] and Hou et al [265] each reported their own newly developed sorbent to have ashorter half-time-i.e.the time it takes to reach half of the asymptotic loading. These half-times were measured under ambient conditions.The half-time provides an easy first assessment of the CO 2 absorption kinetics.T oprovide afair comparison of the half-times of different sorbents for CO 2 capture from ambient air, the half-time should be measured under ambient conditions (400 ppm CO 2 ).…”
Section: The Advantages and Disadvantages Of Moisture-swing Sorbentsmentioning
confidence: 99%
“…Increasing the porosity and specific surface area of fibers can be accomplished with improving the performance of absorption, catalysis, sensors, and so on. Therefore, porous fibers have presented extensive use in a wide variety of applications …”
Section: Secondary Surface Morphologies Of Electrospun Nanofibersmentioning
confidence: 99%
“…In der Studie wird behauptet, dass dieser neue Sorbent eine schnellere CO 2 ‐Sorptionsrate als andere Sorbenten aufweist, über die bis zu diesem Zeitpunkt berichtet wurde . Seitdem haben Armstrong et al., Song et al . und Hou et al .…”
Section: Sorbenten Zur Gewinnung Von Co2 Aus Der Umgebungsluftunclassified
“…Verfahrensprotokolle zum Aufpfropfen von Polymeren auf Ruß (oben), zur Herstellung von Matieralien mit kolloidalen Kristalltemplaten (Mitte) und zur Synthese von Materialien auf HIPE-Basis (unten). [257] Angewandte Chemie strong et al, [263] Song et al [264] und Hou et al [265] berichten, dass ihre eigenen, neu entwickelten Sorbenten eine kürzere Halbwertszeit -d.h.die Zeit, die bençtigt wird, um die Hälfte der asymptotischen Beladung zu erreichen -aufweisen. Diese Halbwertszeiten wurden bei Umgebungsbedingungen gemessen.…”
Section: Vor-und Nachteile Von Feuchtigkeitswechsel-sorbentenunclassified